Respuesta :
The n-th term is given by
[tex]a_n=a_1\cdot r^{(n-1)}\qquad\text{where r is the common ratio}[/tex]
Then we can find the common ratio from the given terms.
[tex]\dfrac{a_4}{a_1}=\dfrac{a_1\cdot r^{(4-1)}}{a_1}=r^3=\dfrac{-16}{1024}=\left(\dfrac{-1}{4}\right)^3\\\\r=\dfrac{-1}{4}\\\\a_6=1024\left(\dfrac{-1}{4}\right)^5=-1[/tex]
The appropriate choice is -1.
Answer:
Option 3rd is correct
[tex]a_6 = -1[/tex]
Step-by-step explanation:
The nth term for the geometric sequence is given by:
[tex]a_n = a_1 \cdot r^{n-1}[/tex]
where,
[tex]a_1[/tex] is the first term
r is the common ratio
n is the number of terms.
As per the statement:
[tex]a_1 = 1024[/tex]
[tex]a_4 = -16[/tex]
For n = 4, we have;
[tex]a_4 = a_1 \cdot r^3[/tex]
⇒[tex]-16 = 1024 \cdot r^3[/tex]
Divide both sides by 1024 we have;
[tex]-\frac{1}{64} =r^3[/tex]
⇒[tex]r =\sqrt[3]{-\frac{1}{64}}=\sqrt[3]{-\frac{1}{4^3}}[/tex]
⇒[tex]r = -\frac{1}{4} = -0.25[/tex]
We have to find the value of 6th term.
for n = 6
[tex]a_6 = 1024 \cdot (-0.25)^5 = 1024 \cdot (-0.0009765625) = -1[/tex]
⇒[tex]a_6 = -1[/tex]
Therefore, the 6th term of the geometric sequence is, -1